Effect of Guide Blade Opening on Cavitation Level at the Inlet Side of the Vertical Francis Turbine Suction Pipe Unit 4 Stairway Hydroelectric Power Plant at PT Inalum Power Plant - Solomon PT Sinaga (Trigin Publisher, 2021)
PLTA Tangga P.T. Inalum Power Plant is one of company that has thelargest power plant in Indonesia. Type of turbine which is used by that company is Vertical Francis Turbine which has problems in operation. One of kind problems is cavitation. Cavitation is the process of forming water bubbles on turbine because of water pressure on turbine drop becomes vapor pressure, that effects vibrations,erosion, and efficiency drop. Cavitation phenomenon can be predicted and be avoided by calculating the cavitation level of turbine, is a comparison of actual Thoma number and critical Thoma number. Cavitation level that is observed is in Entrance of Vertical Francis Turbine Draft Tube Unit 4 PLTA Tangga P.T. Inalum Power Plant. Cavitation level as the dependent variable that is searched for the influence to Guide Vane Opening (GVO) as the independent variable in this experiment. The total of GVO that is used in this experiment is nine variation, there are 102 mm; 132 mm; 161 mm; 168 mm; 176 mm; 183 mm; 186 mm; 191 mm; and 195 mm. Based on this experiment, we can know the cavitation level on every GVO. The highest cavitation level in this experiment is 0.96867 on GVO 195 mm, meanwhile the lowest cavitation is 0,81005 on GVO 102 mm. The entrance of the draft tube can happen the cavitation if the cavitation level is more than 1 or actual Thoma number is more than critical Thoma number. Cavitation can not happen on it if the cavitation level is less than 1 or actual Thoma number is less than critical Thoma number. So the best GVO for avoiding cavitation in the Entrance of Vertical Francis Turbine Draft Tube Unit 4 PLTA Tangga P.T. Inalum Power Plant is 102 mm because it has the lowest cavitation level, meanwhile the GVO that is avoided and the most vulnerable cavitation is 195 mm because it has the highest cavitation level.